Nevus Lipomatosus Cutaneous Superficialis with a Histopathological Appearance Resembling Sclerotic Fibroma: A Rare Case Report - Ruray, Rizka Ramadhani; Djawad, Khairuddin; Nurdin, Airin (Open Access Macedonian Journal of Medical Sciences, 2021)
Background: Nevus lipomatosus cutaneous superficialis (NLCS) of Hoffmann–Zurhelle is a benign idiopathic hamartoma. There are two types of NLCS, multiple and solitary. They are found in the abdomen, lower back, buttocks, hips, upper posterior thighs, and pelvis. The diagnosis can be evaluated with a typical histopathological of mature fat cells in the dermis, with 10%–50% of the dermis. Case Report: We reported a case of NLCS with clinical papules and multiple nodules on the buttocks since the age of 6 years with a history of lipoma removal. The dermoscopic examination was conducted to confirm the diagnosis. The histopathological examination showed a dominant sclerotic fibroma with two sessions of biopsy and a few mature fats on the dermis after deeper cuts paraffin block. Cryotherapy with an open spray method is treatment of choice in this patient. Discussion: The appearance of the dermis in NLCS can be normal or an increase in collagen. Interestingly, collagen has sclerosis partially and resembles sclerotic fibroma never been reported. NLCS increases the amount of collagen; however, collagen as sclerosis remains obscure. The features of NLCS histopathological with other morphological abnormalities in the dermis have been reported, such as NLCS with perifollicular fibroma (PF) features. The sclerotic fibroma features are other morphological abnormalities in NLCS, as reported in the PF.